Online Brazilian Journal of Nursing is a resource for authors - Isabel CF da Cruz (Online Brazilian Journal of Nursing, 2007)
The Online Brazilian Journal of Nursing is delighted to receive articles for publication in all of these categories from nurses and others health professionals